Vietnam’s Post-COVID Resilience: Potential Market for Attracting Foreign Direct Investment - Tran My Hai Loc (Contemporary Research in Business, Management and Economics Vol. 6, 2024)
The COVID-19 pandemic has caused an unprecedented disruption in the global economy, comparable only to the Great Depression of 1930. Many international organizations have acknowledged Vietnam as one of the most attractive investment destinations post-pandemic. Vietnam is highly esteemed by the international community for its effective pandemic containment measures, instilling confidence in foreign investors to engage in business and investment activities. Furthermore, Vietnam is categorized among the least affected countries by the pandemic, with forecasts indicating its ability to weather the global economic downturn successfully. Vietnam’s appeal for foreign direct investment is growing, propelled by its competitive advantages and strategic positioning, particularly its skilled workforce and favorable business environment. Economic recovery indicators are evident, with a robust 6.72% GDP growth in Q4 2023 contributing to an annual 5.05% growth. The National Assembly has set an optimistic GDP growth target of 6.0% to 6.5% for 2024, reflecting confidence in Vietnam’s economic revitalization. This study employs a qualitative research approach and addresses significant questions, such as how Vietnam can quickly overcome the impact of the COVID-19 pandemic and how Vietnam has attracted foreign FDI post-COVID-19. The paper finds that firstly, Vietnam has an effective anti-epidemic model and experience from the SARS pandemic in 2003; second, the Government has had timely policies to gradually support businesses and people to overcome the difficulties of the COVID-19 pandemic, so the economy gradually recovered and became an ideal destination for FDI from major powers; and thirdly, Vietnam’s strategic location grants it unparalleled access to diverse markets and positions it as a prime location for businesses looking to establish a foothold in Southeast Asia. It concludes that a stable business environment and Vietnam’s economic growth potential will make it an attractive destination for foreign investors in the future.